Adaptive reuse of the structure for office buildings into multi-family housing - Hecker, Morgan J. (My University, 2025)
The conversion of vacant office buildings into residential housing offers a sustainable and cost-effective solution to rising urban vacancies and the housing crisis. This report evaluates the feasibility and environmental impact of the structural adaptive reuse compared to new construction, highlighting its potential to reduce greenhouse gas emissions, minimize material waste, and improve affordability. A case study of a four-story office building in Kansas City, Missouri, evaluates sustainability metrics using the Embodied Carbon in Construction Calculator (EC3) and cost analyses based on RS Means data. Findings reveal that the structural adaptive reuse can reduce embodied carbon emissions by approximately eighty-four percent and significantly lower construction costs compared to new developments. Additionally, key structural modifications – such as load adjustments, material reuse, and code compliance – are examined to determine practical implementation challenges and solutions. This research highlights the broader implications of office-to-housing conversions in meeting sustainability goals, reducing urban sprawl, and promoting long-term economic and environmental benefits.
Keywords: Adaptive; Reuse